Red deer in Italy: recent changes in range and numbers - Stefano Mattioli; Pier Giuseppe Meneguz; Alessandro Brugnoli; Sandro Nicoloso (Hystrix, the Italian Journal of Mammalogy, 2001)
Abstract The following paper illustrates changes in distribution range and population size of the red deer Cervus elaphus in Italy in the last three decades. It mentions the main events of reintroduction and restocking together with hunting statistics. The mean yearly increase from 1970 to 1998 was 6% in range and 8% in population size: in 28 years the range had a five fold and the numbers a tenfold incrase. In 1998 the total red deer population in Italy was estimated at 32,000 head, of which 75% are in the central and eastern Alps. In the central and eastern Alps the current population derives mainly from spontaneous recolonisation from neighbouring countries. In the western Alps the contribution of reintroduction prevails. In the northern and central Apennines the present occurrence of red deer is exclusively due to reintroduction. In Sardinia C. e. corsicanus is recovering gradually. The autochthonous nucleus from Mesola Wood needs a long term conservation plan.